The Dance of "Old" and "New" in Chinese Print Culture, 1860s-1955. Issue 3 (11th October 2017) - Brokaw, Cynthia
Argument: Scholars of modern Chinese publishing and book culture focus on the dramatic transformations that took place in the late nineteenth and early twentieth centuries: the new technologies that enabled "mass" printing and the development of "modern" genres of print. They often neglect the fact that xylography remained a working technology through much of the Republican period and even into the People's Republic of China. Here I examine the continued use of woodblock printing and the continuing popularity of "traditional" textual genres from two perspectives. First, from a "bottom up" perspective, I examine the production and sale of woodblock texts in rural markets, often in the face of efforts by both the Republic and the People's Republic to prohibit their use. Second, from a perspective from the top, I consider the deliberate choices made by the government, some elite book collector-publishers, and Daoist and Buddhist devotees to print certain works xylographically.